NÍSIA FLORESTA: KNOWLEDGE AS A SOURCE OF EMANCIPATION IN THE FEMALE CITIZENSHIP TRAINING - Elaine Teresinha Dal Mas Dias, Cleide Rita Silvério de Almeida, (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
This article presents Nísia FLoresta’s life and work, her influence on the educational practice in the nineteenth century and the impact of her proposals today. She represents the female emancipation through knowledge and denounced the injustices imposed on women at that time. Her debates articulated dialogue between European ideas and the Brazilian context. Her critical verve allowed to examine the world, not as something given but as a place of disclosures, review the education practice and resent about it, showing the place assigned to women, and consequently she stated her viewpoint about how that would be possible to be transformed.